Pemeriksaan Pajak: Memahami Hak dan Kewajiban dalam Proses Pengujian Kepatuhan: Penelitian - Daniel Reynaldi L Tobing; Wilma Silalahi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study examines the regulatory framework and practical implementation of taxpayers’ rights and obligations, as well as the authority of tax officials, in the tax audit process as a primary instrument for compliance testing within Indonesia’s taxation system. Tax audits play a strategic role in balancing state revenue interests with the protection of taxpayers’ rights. Therefore, the legal framework provided in the General Provisions and Tax Procedures Law (UU KUP), Law No. 7 of 2021 on Harmonization of Tax Regulations (UU HPP), and implementing regulations such as Minister of Finance Regulation No. 17/PMK.03/2013 serves as an essential foundation for ensuring transparency, accountability, and legal certainty. This study assesses how these regulations are applied in practice, including the effectiveness of the right to information, the right to provide opinions, the obligation to provide documents, and the authority of tax officials during audits. The analysis reveals that although the normative framework is comprehensive, its practical implementation still faces challenges such as information asymmetry, varied administrative readiness of taxpayers, and inconsistent application of audit procedures by tax officials. Fair tax audits require strengthening the capacity of the tax authorities, digital optimization, and continuous education, while ensuring legal protection for taxpayers.